2013
DOI: 10.4049/jimmunol.1201426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycogen Synthase Kinase-3 Increases NKG2D Ligand MICA Expression and Sensitivity to NK Cell–Mediated Cytotoxicity in Multiple Myeloma Cells: Role of STAT3

Abstract: Engagement of NKG2D and DNAX accessory molecule-1 (DNAM-1) receptors on lymphocytes plays an important role for anticancer response and represents an interesting therapeutic target for pharmacological modulation. In this study, we investigated the effect of inhibitors targeting the glycogen synthase kinase-3 (GSK3) on the expression of NKG2D and DNAM-1 ligands in multiple myeloma (MM) cells. GSK3 is a pleiotropic serine-threonine kinase point of convergence of numerous cell-signaling pathways, able to regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 54 publications
7
54
0
1
Order By: Relevance
“…[32][33][34][35][36][37] To this regard, our group has demonstrated that a number of therapeutic drugs, including genotoxic agents, can boost the expression of NKG2D and DNAM-1 ligands on MM cells in vitro and ex vivo, and can enhance NK cell antitumor activity. 25,28,[38][39][40][41] Moreover, our findings also show that the enhanced expression of activating ligands on MM cells after the administration of genotoxic drugs such as doxorubicin and melphalan at doses that fail to induce apoptosis, is mediated by the DDR activation via ATM/ATR, and is associated with a drug-induced tumor cell senescent phenotype. 28,41 In this study, we explored the possibility to induce in vivo cellular senescence of tumor cells upon genotoxic drug treatment in a mouse model of MM resembling the human disease, and we evaluated the contribution of NK cells to the immune surveillance of MM cells in mice treated with low doses of melphalan.…”
Section: Introductionsupporting
confidence: 65%
“…[32][33][34][35][36][37] To this regard, our group has demonstrated that a number of therapeutic drugs, including genotoxic agents, can boost the expression of NKG2D and DNAM-1 ligands on MM cells in vitro and ex vivo, and can enhance NK cell antitumor activity. 25,28,[38][39][40][41] Moreover, our findings also show that the enhanced expression of activating ligands on MM cells after the administration of genotoxic drugs such as doxorubicin and melphalan at doses that fail to induce apoptosis, is mediated by the DDR activation via ATM/ATR, and is associated with a drug-induced tumor cell senescent phenotype. 28,41 In this study, we explored the possibility to induce in vivo cellular senescence of tumor cells upon genotoxic drug treatment in a mouse model of MM resembling the human disease, and we evaluated the contribution of NK cells to the immune surveillance of MM cells in mice treated with low doses of melphalan.…”
Section: Introductionsupporting
confidence: 65%
“…Enhancement of NK cell-mediated recognition of MM cells was reported by us and other investigators, showing increased surface expression of NKG2DLs on tumor cells following treatment with genotoxic agents (22) or with GSK3, HSP-90, and histone deacetylase inhibitors (23)(24)(25). Importantly, drug-induced expression of these ligands on MM cells was always associated with their ability to trigger increased NK cell degranulation in an NKG2D-dependent manner.…”
mentioning
confidence: 71%
“…Lentivirus production and infection of SKO-007(J3) cells were performed as described previously (20). Postinfection, cells were allowed to expand for 24 h and were then selected for puromycin (1 mg/ml) resistance.…”
Section: Virus Production and In Vitro Transductionmentioning
confidence: 99%
“…A pRL-CMV expression vector was cotransfected each time to normalize DNA uptake. Transfections were carried out using a 4D-Nucleofector System (Lonza) as described previously (20). Luciferase and Renilla activity were read using Dual-Luciferase Reporter Assay and the Glomax Multi Detection System (Promega) following the manufacturer's instructions.…”
Section: Real-time Pcrmentioning
confidence: 99%